Comparison of Laboratory Values Obtained by Phlebotomy versus Saline Lock Devices - Corbo, Jill; Fu, Lequan; Silver, Matthew; Atallah, Hany; Bijur, Polly (Academic emergency medicine, 2007)
Objectives To assess the utility of a peripheral saline lock device (SLD) as an alternative to a second venipuncture for obtaining selected blood samples. Methods This prospective study used a comparative design and was conducted in an urban emergency department (ED). Adult patients with an existing SLD in place who required serial phlebotomy were eligible for inclusion in the study. Each subject had blood samples obtained by venipuncture (control) with a Vacutainer adapter according to standard protocols. Within 5 minutes of obtaining the control samples, a sample was obtained from the patients' SLDs; a tourniquet was applied proximal to the intravenous line, a 5‐mL waste portion was obtained, and a Vacutainer adapter was placed to draw specimens for testing. Each of the paired samples was analyzed for hematocrit, electrolytes, and cardiac enzymes. The Bland‐Altman method was used to analyze the concordance between each pair of measurements. Paired t‐tests for each of the eight laboratory tests were used to assess whether the values were statistically different from each other. The 95% limits of agreement around the mean differences were calculated. Differences between SLD aspirates and venipuncture aspirates also were compared with the federal regulatory standards that ensure reliable and accurate laboratory testing. Results Eighty‐one patients were eligible for the study; in 73 (90.1%; 95% confidence interval [CI] = 81.5% to 95.6%) of the patients, the SLD could be aspirated for testing. The paired t‐tests indicated that there were no statistically significant differences between the mean values of the two methods of testing. Of the 584 paired values analyzed, 35 (6.0%; 95% CI = 4.3% to 8.2%) exceeded the Bland‐Altman limits of agreement, and 43 (7.4%; 95% CI = 5.4% to 9.8%) fell outside the acceptable range determined by the federal regulation of clinical laboratories. Of those values that exceeded the acceptable Bland‐Altman limits of agreement, none would have resulted in clinical intervention. Conclusions Aspirating blood via an SLD is an acceptable method of obtaining serial laboratory values in a group of stable, consenting adult ED patients.